Single production of vectorlike Y quarks at the HL-LHC - V. Cetinkaya (Elsevier, 2021)
We study single production of exotic vectorlike Y quark with electric charge |QY|=4/3 and its subsequent decay at the High Luminosity LHC (HL-LHC). Most of the vector like quark (VLQ) decays have the electroweak W bosons in the intermediate state. Besides their direct productions singly or pairs, the W-bosons are involved in decay chains as a result of the decay of a top quark which contributes to the background. This is particularly the case since vectorlike Y quark, which is estimated to be produced with a high cross-section, can only decay via a W boson and a down type quark (d,s,b). We calculate the cross sections of signal (for different couplings and mass values) and relevant Standard Model (SM) backgrounds. After a fast simulation of signal and background events, estimations of the sensitivity to the parameters (mass range 1000-2500 GeV for coupling value κY=0.5, and mass range 500-2000 GeV for coupling values κY=0.3 and κY=0.15) have been presented at the HL-LHC with centre of mass energy s=14 TeV and integrated luminosity projections of 300 fb−1, 1000 fb−1 and 3000 fb−1.